Identity-Trajectories of Early Career Researchers Unpacking the Post-PhD Experience - McAlpine, Lynn (Palgrave Macmillan UK, 2018)
The book asks how we can make sense of career paths for PhD graduates, something that has rarely been systematically studied. It offers a coherent synthesis of the empirically-based insights that arose from the experiences of 48 early career researchers, who were participants in a 10-year qualitative longitudinal research program. The book has the power to inform other researchers' conceptual and methodological approaches to the study of post-PhD career trajectories. The authors draw on the conceptual lens of 'identity-trajectory', which emerged from their research program, to examine the decision-making processes underpinning the careers of PhD graduates, whether contingent researchers and teachers, assistant professors within the academy or professionals elsewhere. The book highlights the role of personal agency in negotiating academic and non-academic work and careers within broader personal lives. It will be compelling reading for researchers and students working in the areas of Education and Sociology, particularly those with an interest in examining career development and decision-making.